Using High Temperature Gas-Cooled Reactor for Seawater Desalination: Challenges and Opportunities. Issue 1 (November 2020) - Al-Saud, Mishari; Chao, Fang
Abstract: Freshwater availability is a global concern. Thus seawater desalination became a variable solution to that issue. However, most desalination plants are powered by fossil-based energy. That fact drove many countries to find an alternative solution in which nuclear desalination became a consideration for many countries like Japan and Saudi Arabia. Different approaches were considered regarding nuclear-desalination, one of which using a High-Temperature Gas-Cooled Reactor (HTR) as an energy source. This paper discusses the challenges and opportunities of using HTR as an energy source for commercial-scale desalination. The findings show the most critical challenges and opportunities related to the technological, economic, social, environmental, regulatory, and infrastructural aspects of HTR-Desalination.